The Correlation of Body Mass Index and the onset of menarche with the menstrual cycle in young women at Pondok Assalafi Nurul Huda, Sugio District - Martini, Diah Eko; Maghfuroh, Lilis; Aisyah, Harnina Samantha; Sari, Dita Puspita (Universitas Muhammadiyah Lamongan, 2022)
Introduction: Menstruation often occur in adolescent girls where there are menstrual cycles that vary and are not always normal. This can interfere with their lives and activities. Several factors that influence this are nutritional status and onset of menarche. This study aims to determine the correlation between body mass index and the onset of menarche with the menstrual cycle in adolescent girls at Assalafi Nurul Huda Islamic Boarding School, Sugio District.Methods: The research design used correlational analysis with a cross-sectional approach. The population was taken from all young women in Assalafi Nurul Huda Islamic Boarding School, Sugio District with a total population of 69 people. Sampling using Simple Random Sampling the number of samples was as many as 59 people. The instrument used a questionnaire and observations of weight and height and then analyzed using the Spearman Rho test.Results: They oung women who had a normal BMI (18.5–25 kg/m2) mostly had normal menstrual cycles (76.5%), while young women who had a BMI was very thin (<17 kg/m2), thin ( 17–28.5 kg/m2) and obese BMI (25–27kg/m2) mostly had oligomenorrheal menstrual cycles (90%; 96.4%;100%). Spearmen rank test (Rho) has a value of p=0.001, r=0.407. Menarche onset at the age of 11-13 years tends to have a normal menstrual cycle (90%), while the onset of menstruation at the age of <11 years and >13 years tend to have oligominorous menstrual cycles (85.7%; 85.7%) with p-value=000.4, rs: 0.372.Conclusion: There is a correlation between body mass index and the onset of menstruation with the menstrual cycle.